Acute Flaccid Myelitis: A Rare but Devastating Illness. Issue 2 (March 2019) - Beal, Judy A.
Abstract : Acute flaccid myelitis is a rare but devastating illness that predominantly effects children. In January, 2019, the CDC confirmed 186 cases of AFM across 38 states in the United States in 2018, mostly in individuals under 18 years of age. Our pediatric nursing expert, Dr. Beal, provides an update.